Association of Serum Neuron-Specific Enolase and C-Reactive Protein With Disease Location and Endoscopic Inflammation Degree in Patients With Crohn's Disease - Yang, Rui-Xia; Song, Wei-Juan; Wu, Zhi-Qi; Goyal, Hemant; Xu, Hua-Guo (Frontiers in Medicine, 2021)
Objective: To explore the association between serum markers neuron specific enolase (NSE) and C-reactive protein (CRP) with intestinal lesion location and degree of inflammation in patients with CD. Design: The levels of serum NSE, CRP and fecal calprotectin (FC) in patients with CD were analyzed retrospectively. The severity of inflammatory lesions in the intestinal wall was accessed using the Simple Endoscopic Score for Crohn’s Disease (SES-CD). Results: The levels of NSE in patients with CD were higher than that of healthy individuals (14.87ng/mL vs. 12.68ng/mL, P<0.001). The levels of CRP in patients with CD were higher than that of healthy individuals (12.30 mg/L vs 3.40 mg/L, P<0.001). The FC levels in patients with CD were higher than that of patients with non-inflammatory bowel disease (1143.90 μg/g vs. 114.21μg/g, P<0.05). The levels of NSE in CD with ileal lesions, simultaneous ileal and colon lesions were significantly higher than those in patients with CD with colonic lesions. However, the CRP was higher in patients with colonic lesions than those with ileal lesions. The levels of NSE in patients with severe inflammation were higher than the patients with moderate inflammation (15.95 ng/mL vs. 13.89 ng/mL, P<0.05). Similarly, the NSE levels in patients with CD with severe inflammation were higher than the patients with CD with mild inflammation (15.95 ng/mL vs 13.53 ng/mL, P<0.05), The levels of CRP in severe inflammation were higher than those in moderate inflammation (29.80 mg/L vs. 19.60 mg/L, P<0.05). In addition, the CRP levels in severe inflammation were higher than those in mild inflammation (29.80 mg/L vs. 5.86 mg/L, P<0.05). ROC curve analysis showed that when NSE was combined with CRP for distinguishing between patients with CD and those without CD, sensitivity increased to 80.41%, specificity increased to 74.66%, and a highest AUC equal to 0.843. Conclusion: Our study shows that serum NSE and CRP can be used to assess the severity of CD as well as the location of intestinal involvement. Therefore, NSE and CRP could be used as the non-invasive tests to detect the location and severity of disease in patients with CD in daily routine practice.